Investasi Emas di Pegadaian Syariah Berdasarkan Persepektif Hukum Ekonomi Syariah - Aini, Ailia Nur; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
Gold investment is one form of investment that is in demand society because of the stability of its value and its nature as a protected asset mark. From the perspective of sharia economic law, investing in gold is a must fulfill Islamic principles, such as avoiding usury, gharar, and maysir. Sharia Pegadaian offers gold investment services in accordance with sharia through Murabahah and Ijarah schemes Muntahiyah Bittamlik, which provides certainty of ownership without elements of exploitation. This study aims to analyze gold investment mechanism at Sharia Pegadaian and its suitability with sharia economic law. With qualitative descriptive methods,This research reveals that gold investment in Pegadaian Sharia has a more inclusive, transparent and safe system compared to conventional investments. However, challenges such as fluctuations in gold prices remain a necessary factor noticed by investors. Therefore, understanding that in depth regarding sharia economic principles and investment strategies. The right approach is the key to success in sharia gold investment.